Principal components of the 180°-turn with the ball kinematics in youth soccer players - Zago, M.; Codari, M.; Grilli, M.; Sforza, C. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The interpretation of parameters extracted from sophisticated sport-specific techniques is not always straightforward. This is the case of the 180° change of direction with the ball in soccer. The 180°-turn performance of ten Under-13, sub-elite soccer players was recorded by means of a motion capture system. Principal Component Analysis (PCA) was applied to a set of 21 anthropometrics and kinematic variables including center of mass related quantities and joints range of motion. The first three principal components, explaining 61% of the overall variance, were retained and discussed. PCA unveiled the relevant structure of the dataset, describing both movement speed and amplitude issues, and the relationship between body size and the change of direction ability.